Pelaksanaan Show Case Meeting (SCM) pada Proyek Preservasi Jalan Girian – Kema – Rumbia – Buyat 2024 - Martalata, Andi; Thambas, Arthur Harris; Mananoma, Tiny (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Road preservation is a type of maintenance that keeps roads in satisfactory working order by using preventive, corrective, rehabilitation, and reconstruction methods. This approach makes sure that the road stays usable for the entire time it is planned to be used. In practice, preservation projects often run into delays that can lead to important contract conditions. To avoid this, there needs to be a structured way to evaluate things through a Show Case Meeting (SCM). This study looks at how SCM was used in the 2024 Girian–Kema–Rumbia–Buyat Road Preservation Project to find out what caused the delays and how well the agreed-upon fixes worked. The method included looking at physical progress, differences between planned and actual performance, and how well the contractor did during SCM Stages I and II. The results indicate that the contractor failed to provide enough workers and move the right equipment, which led to the critical contract condition. SCM Stage I did not meet the required test-case target, but SCM Stage II did, showing that the contractor was able to meet the required performance targets and finish the work on time. These results show that SCM is an important way to control contracts and fix problems, which helps construction projects get done on time and well.